Reducing Oracle RAC Wait Events by Using Instance-Specific Block Allocation for Production Applications - Natti, Murali (Eastasouth Institute, 2023)
Oracle Real Application Clusters (RAC) is a robust and high-availability solution designed to enable multiple database instances to share the same physical database, offering benefits such as scalability and fault tolerance. However, while Oracle RAC can support critical production environments, it introduces significant complexities, particularly with regard to wait events. One of the primary performance bottlenecks in Oracle RAC is inter-instance communication, commonly referred to as cache fusion, where instances must exchange and synchronize shared data blocks across the cluster. This overhead becomes particularly problematic for production applications that access commonly used tables or objects, leading to increased wait times, slower response rates, and reduced throughput. This paper outlines a novel approach that aims to alleviate Oracle RAC wait events by binding specific application instances to individual Oracle RAC nodes. By allocating frequently accessed tables or objects to specific nodes, this method reduces contention, optimizes database access, and enhances overall application performance.